Você está na página 1de 20

 

 

 

 

 

 

 

 

 

 

 

α =

k

ρc

t xx

k ρ c

T t = α · T xx

i i 1 i + 1

x

t = n · t t n n + 1

θ 0 θ 1

θ = 0

θ = 1

θ = 1/2

n+1 n+1 n+1 n+1 n n n n − T − 2T + T + T
n+1
n+1
n+1
n+1
n
n
n
n
− T
− 2T
+ T
+ T
i
i
i−1
i
i+1
i−1 − 2T
i
i+1
ρc T
− kθ T
− k(1 − θ) T
∆t
∆x 2
∆x 2

= 0

θ

(1 θ + θ) =

1

T t =

α · T xx · (1 θ + θ)

=

α · θ · T xx + α · (1 θ) · T xx

t + ∆t T

i

n+1

t (i,n)

T (x,t+∆t) = T

i

n+1

n

= T

i

+ ∆t · (T t ) n +

i

t 2

2!

(T tt ) n + · · ·

i

(T t ) n =

i

n+1

T i
T
i

T

n

i

t

θ

(i,n + 1) (1 θ)

(i,n)

(i + 1, n) x

(i 1, n)

i x

i+1 = T i

T

n

n

+ ∆x · (T

n

i

) x +

x

2

2!

(T xx ) n +

i

x

3

3!

(T xxx ) n

i

i1 = T i

T

n

n

x · (T

n

i

) x +

x

2

2!

(T xx ) n

i

x

3

3!

(T xxx ) n

i

i+1 + T

T

n

i1 = 2 · T

i

n

n

+ ∆x 2 · (T xx ) n + · · ·

i

+

·

·

·

+

·

·

·

 

(i 1,n + 1) (i + 1,n + 1)

(T xx ) n =

i

(T xx ) n+1

i

=

T i1 2T

n

n

i

+ T

n

i+1

n+1

T

i1

x 2

2T

i

n+1

+ T

n+1

i+1

x 2

T

n+1

i

T

n

i

t

αθ T

n+1

i1

2T

i

n+1

+ T

n+1

i+1

x 2

α(1 θ) T

n

i1 2T

n

i

+ T

n

i+1

x 2

= 0

(i, n)

n+1

T

i

n+1

T

i+1

n+1

T

i1

n

= T

i

n

= T

i

+

t(T t ) n +

i

t 2

2

(T tt ) n +

i

t 3

6

(T ttt ) n

i

+ O(∆t 4 )

+

t(T t ) n +

i

x(T x ) n +

i

1

2

t 2 (T tt ) n +

i

2∆tx(T xt ) n

i

+

x 2 (T xx ) n +

i

O(∆t 2 , x 2 )

n

= T

i

+

t(T t ) n x(T x ) n +

i

i

1

2 t 2 (T tt ) n 2∆tx(T xt ) n +

i

i

x 2 (T xx ) n +

i

O(∆t 2 , x 2 )

i+1 = T i

T

n

n

+ ∆x · (T

n

i

) x +

x

2

2!

(T xx ) n +

i

x 3

3!

(T xxx ) n

i

+

O(∆x 4 )

i1 = T i

T

n

n

x · (T

n

i

) x +

x

2

2!

(T xx ) n

i

x 3

3!

(T xxx ) n

i

+

O(∆x 4 )

n+1

T

i+1

+ T

n+1

i1

2T

i

n+1

= [T

n

i

+ ∆t(T t ) n ] (1 + 1 2) + ∆x(T x ) n (1 1) + ∆x 2 (T xx ) n + O(∆x 4 )

i

i

i

=

x 2 (T xx ) n + O(∆x 4 )

i

i+1 + T

T

n

i1 2T

i

n

n

n

= T

i

(1 + 1 2) + ∆x(T x ) n (1 1) +

i

x 2

2

(2 · (T xx ) n ) + O(∆x 4 )

i

= ∆x 2 (T xx ) n + O(∆x 4 )

i

(Eq.2.10) =

t · T t + t 2

2

T tt + t 3

6

T ttt + O(∆t 4 ) n

i

t

α θ x 2 (T xx ) n + (1 θ) x 2 (T xx ) n ) + O(∆x 4 )

i

i

x 2

= ·T t +

t

2

T tt +

  • 6 T ttt + O(∆t 3 ) n α θ [(T xx ) n ] + (1 θ) [(T xx ) n )] + O(∆x 2 )

t 2

i

i

i

= (T t ) n α(T xx ) n +

i

i

t

  • 2 (T tt ) n + O(∆t 2 , x 2 )

i

T

i

n+1

T

n

i

t

αθ T

n+1

i1

2T

i

n+1

+ T

n+1

i+1

x 2

α(1 θ) T

n

i1 2T

n

i

+ T

n

i+1

x 2

. . .

[(T t ) n α(T xx ) n ] =

i

i

t

2

(T tt ) n + O(∆t 2 , x 2 )

i

ε T

t x 2

t

x

ε T =

t

  • 2 (T tt ) n + O(∆t 2 , x 2 )

i

( T ¯ t ) n α(

i

¯

T xx ) n

i

=

t

2

(

¯

T tt ) n

i

+ O(∆t 2 , x 2 )

( T ¯ t ) n = α(

i

¯

T xx ) n

i

+ O(∆t, x 2 )

(

¯

T tt ) n

i

= α[(

¯

T xx ) t ] n

i

+

O(∆t,

x 2 )

= α[(

¯

T t ) xx ] n

i

+

O(∆t,

x 2 )

(

¯

T tt ) n

i

=

α 2 (

¯

T xxxx ) n

i

+ O(∆t, x 2 )

ε T =

t

2

α 2 (

¯

T xxxx ) n

i

+ O(∆t 2 , x 2 )

( T ¯ t ) n α(

i

¯

T xx ) n

i

+

t

2

α 2 (

¯

T xxxx ) n

i

= O(∆t 2 , x 2 )

n+k

T

i+m

= V n+k · e I(i+m)ϕ

I = 1

(V n+1 V n )e Iiϕ =

αt

x 2

e I(i1)ϕ 2e Iiϕ + e I(i+1)ϕ θV n+1 (1 θ)V n

e Iiϕ

(V n+1 V n ) =

=

αt

x 2

e Iϕ 2 + e Iϕ θV n+1 + (1 θ)V n

αt

x 2

(2 cos(ϕ) 2) θV n+1 + (1 θ)V n

n+1

V n G V

V n

G 1 =

=

2αt

x 2

(cos ϕ 1)(θG + 1 θ)

2αt

x 2

θG(cos ϕ 1) +

2αt

x 2

(1 θ)(cos ϕ 1)

Fo =

αt

x 2

G[1 θ2Fo(cos ϕ 1)]

=

G =

2Fo(1 θ)(cos ϕ 1) + 1

1 + 2Fo(1 θ)(cos ϕ 1)

1 θ2Fo(cos ϕ 1)

(cosϕ 1) = 2sen 2 ( ϕ )

2

G =

=

  • 1 + 2Fo(1 θ)(2sen 2 ( ϕ ))

2

1 θ2Fo(2sen 2 ( ϕ ))

2

  • 1 4Fo(1 θ)sen 2 ( ϕ )

2

1 + 4θFo(sen 2 ( ϕ )

2

= 1

4Fo sen 2 ( ϕ )

2

1 + 4θFo(sen 2 ( ϕ ))

2

|G| ≤ 1

1 G 1

1 G 1

1 1

2 ≤ −

1 + 4θFo(sen 2 ( ϕ ))

4Fo sen 2 ( ϕ )

1 + 4θFo(sen 2 ( ϕ ))

4Fo sen 2 ( ϕ )

1

0 sen 2 ( ϕ ) 1 ϕ

2

2

2 ≤ −

2

2

4Fo sen 2 (ϕ/2)

Fo sen 2 (ϕ/2)(4 8θ)

Fo(1 2θ)

sen 2 (ϕ/2) 1

=

Fo(1 2θ) 1 2

Fo =

αt

x

2

θ

αt

x 2

(1 2 θ)

θ = 0 Fo 1/2

0 < θ < 1 2 (1 2 θ) > 0

θ =

2 (1 2θ) = 0

1

Fo

  • 2 1 < θ 1 (1 2θ) < 0

Fo

θ

θ = 1/2

 

 

 

 

 

 
 

 

 
 

 

 

 

 

 

 

 

 

 

 

 

 
 

L = 0,24m α = 1,5 10 6

T (x=0,t) = 25 o C

 

T (x=L,t)

= 25 o C

T (x,0) = 25 + 5sen( πx )

L

θ = 0 θ = 1/2 θ = 1 x = 1mm Deltat = 30s

θ = 0

θ = 0
θ = 0
θ = 0.5
θ = 0.5

t

θ = 0.5

θ Fo = 0 . 6 > 0 . 5

θ

θ Fo = 0 . 6 > 0 . 5

θ Fo = 0 . 6 > 0 . 5

Fo = 0.6 > 0.5

∆t = 200s
∆t = 200s
∆t = 200s ∆ t = 1000 s ∆ t θ = 1 ∆ x

t = 1000s

t

θ = 1

x 2 t

∆t = 200s ∆ t = 1000 s ∆ t θ = 1 ∆ x

T (x=0,t) = 0 o C

T (x=L,t) = 0 o C

T (x,0) = 25 o C

θ = 0

θ = 1/2 θ = 1

x = 1mm t = 30s

θ

θ = 0

θ = 0
θ = 0
( x =0 ,t ) ( x = L,t ) • T = 25 C

θ = 0.5

θ = 1
θ = 1

Fo ≥ 1 / 2 T = α · T     

Fo 1/2

T t = α · T xx

T (x=0,t)

T (x=L,t)

T (x,0)

= T 0

= T 0

= f (x)